Heart Rate Variability and Salivary Biomarkers Differences between Fibromyalgia and Healthy Participants after an Exercise Fatigue Protocol: An Experimental Study - Ana Rodrigues Costa; Ana Freire; Jose A. Parraca; Vanda Silva; Pablo Tomas-Carus; Santos Villafaina (Diagnostics, 2022)
Previous studies showed that people with Fibromyalgia (FM) suffer from dysautonomia. Dysautonomia consists of persistent autonomic nervous system hyperactivity at rest and hyporeactivity during stressful situations. There is evidence that parameters reflecting the complex interplay between the autonomic nervous system and the cardiovascular system during exercise can provide significant prognostic information. Therefore, this study aimed to investigate the differences between people with FM and healthy controls on heart rate variability (HRV) and salivary parameters (such as flow, protein concentration, enzymatic activities of amylase, catalase and glutathione peroxidase) in two moments: (1) at baseline, and (2) after an exercise fatigue protocol. A total of 37 participants, twenty-one were people with fibromyalgia and sixteen were healthy controls, participated in this cross-sectional study. HRV and salivary samples were collected before and after an exercise fatigue protocol. The fatigue protocol consisted of 20 repetitions of knee extensions and flexions of the dominant leg at 180 °·s−1 (degrees per second). Significant differences were found in the HRV (stress index, LF and HF variables) and salivary biomarkers (with a higher concentration of salivary amylase in people with FM compared to healthy controls). Exercise acute effects on HRV showed that people with FM did not significantly react to exercise. However, significant differences between baseline and post-exercise on HRV significantly induce alteration on the HRV of healthy controls. Catalase significantly increased after exercise in healthy controls whereas salivary flow significantly increased in women with FM after an exercise fatigue protocol. Our study suggests that a higher α-amylase activity and an impaired HRV can be used as possible biomarkers of fibromyalgia, associated with a reduction in salivary flow without changes in HRV and catalase activity after a fatigue exercise protocol. More studies should be carried out in the future to evaluate this hypothesis, in order to find diagnostic biomarkers in fibromyalgia.